LEXICAL KNOWLEDGE IN INSTRUCTED LANGUAGE LEARNING: THE EFFECTS OF AGE AND EXPOSURE - Miralpeix, Inmaculada (International Journal of English Studies, 2009)
The aim of this study is to analyse the possible effects of Age of Onset (AO), Cognitive Maturity (Age at Testing-AT-) and Amount of Exposure (AE) on the productive vocabularies of learners of English as a Foreign Language (FL). Three groups of bilingual Catalan/Spanish students were tested towards the end of Secondary Education. The groups differed in AO (8 vs. 11 years), AT (16 vs.17) and AE (726 vs. 800 hours). They performed four different tasks: three oral (an interview, a storytelling and a roleplay) and one written (a composition). The tasks were analysed with measures extrinsic to the learners’ production. Firstly, their Lexical Frequency Profiles were computed with VocabProfile (Nation, 1995). Secondly, P_Lex (Meara, 2001) was used to assess the lexical richness of the texts. Furthermore, Anglo-Saxon and Greco-Latin Cognate indices were obtained for each of the tasks. Results show that an early AO does not necessarily suppose an advantage for Early Starters (ES), as Late Starters’ (LS) productive vocabularies are very similar to those of their younger peers.